2018
DOI: 10.18520/cs/v115/i7/1379-1386
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Cytological, Palynological and Molecular Characterization of Certain <i>Mangifera</i> Species

Abstract: A. M., Effect of irrigation intervals and potassium application methods on yield and yield components of wheat crop irrigated with surge flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Despite differences between these three approaches, the relationships between most groups were well resolved and highly supported, suggesting that the use of chloroplast genome data does significantly improve the resolution of phylogenetic analysis. Previous studies have revealed the genetic relationship of Mangifera through morphological, nuclear, amplified fragment length polymorphism, ribosomal internal transcribed spacer (ITS), and partial chloroplast gene analysis ( Eiadthong et al, 2000 ; Nishiyama et al, 2006 ; Sankaran et al, 2018 ; Yonemori et al, 2002 ). The whole chloroplast genome sequence-based phylogenetic tree was built to explore the evolutionary similarities/differences between Mangifera species and between genera in the Sapindales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite differences between these three approaches, the relationships between most groups were well resolved and highly supported, suggesting that the use of chloroplast genome data does significantly improve the resolution of phylogenetic analysis. Previous studies have revealed the genetic relationship of Mangifera through morphological, nuclear, amplified fragment length polymorphism, ribosomal internal transcribed spacer (ITS), and partial chloroplast gene analysis ( Eiadthong et al, 2000 ; Nishiyama et al, 2006 ; Sankaran et al, 2018 ; Yonemori et al, 2002 ). The whole chloroplast genome sequence-based phylogenetic tree was built to explore the evolutionary similarities/differences between Mangifera species and between genera in the Sapindales.…”
Section: Resultsmentioning
confidence: 99%
“…There are 69 species of mango in the world that are mainly distributed in tropical and subtropical countries including India, Indonesia, the Malay Peninsula, Thailand, and South China, of which, five species are grown in China, namely M. indica, M. persiciformis, M. longipes, M. hiemalis, and M. sylvatica ; however, the varieties cultivated in production belong to M. indica . Phylogenetic analysis of Mangifera species has been a hot topic of research ( Nishiyama et al, 2006 ; Sankaran et al, 2018 ), while the whole chloroplast genome sequences can provide more genetic information and higher species resolution ability than other molecular data. However, the chloroplast genomes of most Mangifera plants remain unknown ( Azim, Khan & Zhang, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have uncovered the genetic relationships among the Mangifera species through morphological, nuclear, internal ribosomal transcribed spacer (ITS), ampli ed fragment length polymorphism (AFLP), and chloroplast gene analyses [34,[36][37][38][39]. Plant mitochondria have evolved rapidly, resulting in heterogeneity, large-scale genomic reorganization, and gene mosaicism in the mitochondrial genomes of various species [25,40].…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences between these three approaches, the relationships between most groups were well resolved and highly supported, suggesting that the use of chloroplast genome data does significantly improve the resolution of phylogenetic analysis. Previous studies have revealed the genetic relationship of Mangifera through morphological, nuclear, amplified fragment length polymorphism, ribosomal internal transcribed spacer (ITS), and partial chloroplast gene analysis (Eiadthong et al 2000;Nishiyama et al 2006;Sankaran et al 2018;Yonemori et al 2002). The whole chloroplast genome sequencebased phylogenetic tree was built to explore the evolutionary similarities/differences between Mangifera species and between genera in the Sapindales.…”
Section: Phylogenetic Relationship Of Chloroplast Genomesmentioning
confidence: 99%
“…Phylogenetic analysis of Mangifera species has been a hot topic of research (Nishiyama et al 2006;Sankaran et al 2018), while the whole chloroplast genome sequences can provide more genetic information and higher species resolution ability than other molecular data. However, the chloroplast genomes of most Mangifera plants remain unknown (Azim et al 2014).…”
Section: Introductionmentioning
confidence: 99%